2019
DOI: 10.1097/ipc.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Burkholderia cepacia Prosthetic Mitral Valve Endocarditis and Literature Review

Abstract: Burkholderia cepacia prosthetic valve endocarditis (PVE) is extremely rare, with few cases in the literature. A report of a patient with PVE is described, followed by a literature review on B. cepacia PVE. A 38 year old man with poor dentition and a history of intravenous drug use (IVDU) and mitral valve replacement was found to have a mitral valve vegetation. Five sets of blood cultures on different days grew B. cepacia. Individual sets of blood cultures on different dates also isolated S. viridans (outside h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Casalta et al 6 reported a case of PVE caused by P. luteola after cardiac surgery leading to replacement of the aortic bioprosthetic valve. Similar reports of other Pseudomonas species prosthetic valve infections, 711 as shown in Table 1, have been reported in the literature with a noted common theme of increased morbidity and mortality. While Pseudomonas species are rarely implicated as a cause, P. aeruginosa is the most common isolated pathogen.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Casalta et al 6 reported a case of PVE caused by P. luteola after cardiac surgery leading to replacement of the aortic bioprosthetic valve. Similar reports of other Pseudomonas species prosthetic valve infections, 711 as shown in Table 1, have been reported in the literature with a noted common theme of increased morbidity and mortality. While Pseudomonas species are rarely implicated as a cause, P. aeruginosa is the most common isolated pathogen.…”
Section: Discussionsupporting
confidence: 85%
“…While Pseudomonas species are rarely implicated as a cause, P. aeruginosa is the most common isolated pathogen. 2,411…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that patients infected with Burkholderia cepacia were predominantly detected in the Internal Medicine wards. B. cepacia is known to cause various diseases and is often found in patients with a history of conditions that affect the function of internal organs, such as cystic fibrosis ( 7 , 8 ), infectious endocarditis ( 20 ), and chronic granulomatous disease ( 10 ). In addition to the internal medicine wards, patients treated in ICU rooms also had a higher number of B. cepacia isolates during the study, similar to previous research showing a higher occurrence of B. cepacia in ICU rooms compared to non-ICU rooms ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endocarditis caused by BCC was more commonly reported for patients with prosthetic valves ( 37 ) and for patients with a history of injection drug use and native valve involvement ( 38 ). Patient 3 exhibited the clinical features of right-sided endocarditis.…”
Section: Discussionmentioning
confidence: 99%